2009
DOI: 10.2203/dose-response.09-036.chiang
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Optimal Selenium Dose for Prostate Cancer Risk Reduction: Insights from the U-Shaped Relationship between Selenium Status, DNA Damage, and Apoptosis

Abstract: ᮀ Our work in dogs has revealed a U-shaped dose response between selenium status and prostatic DNA damage that remarkably parallels the relationship between dietary selenium and prostate cancer risk in men, suggesting that more selenium is not necessarily better. Herein, we extend this canine work to show that the selenium dose that minimizes prostatic DNA damage also maximizes apoptosis-a cancer-suppressing death switch used by prostatic epithelial cells. These provocative findings suggest a new line of think… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 65 publications
1
26
0
Order By: Relevance
“…The ability to produce ROS explains dose dependent toxic effects of Se, observed in vitro and in vivo [108] and is considered to underlie its genotoxic [113,114] and proapoptotic activity [115][116][117]. However, some of these dose dependent effects, specifically DNA damage and apoptosis, were observed in vivo after treatment with SeMet, which is a Se compound regarded as nontoxic due to the inability to generate ROS [118][119][120]. Notably, the same compound was used in SELECT, and since SELECT has clearly indicated toxicity of supranutritional level of SeMet in humans, it is probable that detrimental effects of this particular organic Se compound observed in that trial were not related to the ability to produce ROS.…”
Section: Biochemical Evidencementioning
confidence: 99%
“…The ability to produce ROS explains dose dependent toxic effects of Se, observed in vitro and in vivo [108] and is considered to underlie its genotoxic [113,114] and proapoptotic activity [115][116][117]. However, some of these dose dependent effects, specifically DNA damage and apoptosis, were observed in vivo after treatment with SeMet, which is a Se compound regarded as nontoxic due to the inability to generate ROS [118][119][120]. Notably, the same compound was used in SELECT, and since SELECT has clearly indicated toxicity of supranutritional level of SeMet in humans, it is probable that detrimental effects of this particular organic Se compound observed in that trial were not related to the ability to produce ROS.…”
Section: Biochemical Evidencementioning
confidence: 99%
“…The same authors showed much lower selenium concentrations in cancer patients compared to the control group. The antioxidant properties of selenium and glutathione peroxidase and their role in DNA protection are used in anti-cancer therapy [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Se levels required to maintain DNA integrity have been previously evaluated in dog prostate cancer models [54,55]. These studies have shown that the DNA damage variation (evaluated by the single cell gel electrophoresis or Comet assay) produced a 'U' shaped curve, indicating increased DNA damage at both the extreme ends of the Se spectrum.…”
Section: Introductionmentioning
confidence: 99%